Qualidade física e fisiológica de sementes de soja em função de teores de água da semente e rotações do cilindro na colheita - Nogueira, Patricia (2020)
The objective of this work was to evaluate whether the quality of soybean seeds is affected by the water content (TA) of the seed and rotating cylinder rotations (RCT) in the harvest and also in the storage, establishment of plants and yield in the following harvest. The harvest of the cultivar BMX Turbo RR® occurred in the 2017/2018 crop when the seed reached two TA, 15% and 12%., In four rotations of the harvester cylinder (RCT) (450, 600, 750 and 900 rpm) of the harvester. Right after the harvest, part of the seed with 15% TA was subjected to drying up to 12% (TA 15-12%). Thus, the experimental design was randomized blocks in a bifactorial scheme, three TA x four RCT, in three replications. The harvested seed was evaluated for its physical quality attributes: purity test (SP) (%), percentage of broken seeds (SQ) (%), hypochlorite (H) (%); and physiological quality attributes: first count in the germination test (PCG) (%), germination test (G) (%), shoot length (CPA) (cm), root length (CR) (cm), accelerated aging test (EA) (%), tetrazolium (TZ) (%) and electrical conductivity (EC) (μS/cm/g). G and vigor tests were also performed at 90 and 180 days of storage. After, in the 2018/19 harvest, the seed from harvest and storage in 2018 was sown in the field, following the same experimental design, with three replications. G (%), emergency speed index (IVE) (%), emergency speed (VE) (%), thousand seed weight (PMS) (g) and productivity (P) (kg.ha- 1). The harvest in different water levels and rotations does not affect the G% of seeds, as the vigor (%) decreases with the increase in RCT. Seed harvested with TA 12% has a higher G% after storage. Seed TA and harvest RCT do not affect, after storage, G, IVE, VE, PMG and soybean yield evaluated in the field.